Comparison of Autologous Blood Coagulum (ABC) and Suture at Recurrence Rate and Graft Stability of Postoperative Primary Pterygium Using Conjunctival Autograft: A Meta-Analysis From Randomized Controlled Trial - Amelia Rahmah Kartika; Made Angga Putra; Delfitri Lutfi (Vision Science and Eye Health Journal, 2022)
Introduction: The main challenge of pterygium management is the postoperative recurrence rate. Currently, the use of surgical sutures for conjunctival autograft fixation, which has prolonged surgery duration, has a risk of increased inflammation and infection. Recently, some reports about autologous blood coagulum (ABC) for conjunctival autograft fixation. This technique has a minimal cost and minimal risk of infection. Purpose: The study aimed to evaluate the postoperative recurrence rate and graft stability after using ABC and sutures. Methods: A systematic research was done on Pubmed, Cochrane Library, and Science Direct online databases for all relevant randomized controlled trials (RCTs) up to 18 July 2020. The collected RCTs were independently screened and identified to match the inclusion criteria. The relevant data were compiled in population, intervention, control, outcomes (PICOs) format and analyzed with Review Manager 5.3 software. Results: Nine RCTs involving a total of 764 patients were assessed. The primary outcome indicates that ABC significantly reduced the recurrence rate compared to sutures (RR = 0.51, 95% CI 0.27 to 0.98, p = 0.04). Meanwhile, in graft stability, the suture was statistically better than ABC (RR = 1.95, 95% CI 1.27 to 3.01, p = 0.002). As a secondary outcome, the duration of surgery was significantly shorter in ABC than in sutures (MD -15.22, 95% CI -22.57 to -7.88, p<0.0001). Conclusions: Although the graft is less stable, ABC may be a promising approach after pterygium excision. The use of autologous blood for conjunctival autograft fixation in primary pterygium was associated with a lower recurrence rate and shorter duration of surgery.